Assessing Benefits of Neighborhood Walkability to Single-Family Property Values: A Spatial Hedonic Study in Austin, Texas. (December 2015) - Li, Wei; Joh, Kenneth; Lee, Chanam; Kim, Jun-Hyun; Park, Han; Woo, Ayoung
This article investigates the impact of neighborhood walkability, measured by Street Smart Walk Score and sidewalk density, on property values by analyzing the 2010–2012 single-family home sale transactions in Austin, Texas. The Cliff-Ord spatial hedonic model (also known as the General Spatial Model, or SAC) is used to control for spatial autocorrelation effects. Results show that improving walkability through increased access to amenities in car-dependent neighborhoods does not appear to increase property values; adding sidewalks in these neighborhoods leads to a minimal increase in property values. Investments in neighborhood amenities and sidewalks will yield a greater home price increase in a walkable neighborhood than in a car-dependent neighborhood.